Effect of surfactants on mass transfer in a bubble column equipped with a horizontal tube bundles. (April 2020) - Al-Shahrani, S.S.; Nosier, S.A.; El-Shazly, A.H.; Abdel-Aziz, M.H.
Abstract: The influence of sodium lauryl sulfate (anionic surfactant) on the solid- liquid mass transfer coefficient in a gas sparging system prepared with a tube bundles is considered. Diffusion - controlled dissolution approach of copper in acidified dichromate solution was employed. Parameters examined are the concentration of surfactant, superficial gas velocity and the number of actively exposed tube bundles (ranging from 1–5). The presence of surfactant decreased the mass transfer coefficient by an extent ranges from 13 to 46% contingent on the concentration of surfactant. The governing parameters are interrelated by a dimensionless correlation and an approach was suggested to use it in design, scale up and predicting the performance of the gas sparged tube bundle under various conditions. The benefits and shortcomings of using surfactants in bubble columns are discussed in terms of energy conservation and reduction in mass transfer, respectively.